Pengaruh Suplementasi Daun Sengon (Albazia falcataria) Terhadap Kecernaan dan Fermentabilitas Bagasse Hasil Amoniasi Secara In Vitro - Suryadi, Suryadi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The  objective  of  the  research  was  to  study  the  influence  of    sengon  leaf  supplementation  on  the  digestibility  and  fermentability of  urea  treated  bagasse using with  in  vitro  technique.  The  matter  were used in the research was the bagasse-urea treated which had good degradation characteristic which origin from the first  research.  Completely  randomized design with five treatments of 0%, 5%, 10%, 15%  and 20%  sengon  leaf  supplementation    and  four  replications  were  used  in    this  experiments.    Parameter measured were the dry metter  and organic matter digestibility, acidity degree,  ammonia (N-NH3) and VFA production of in vitro  test.  The result showed that the sengon leaf supplementation was significant effect  (P>0.05) on the  digestibility and fermentability  bagasse-urea treated with in vitro technique. It could be concluded that bagasse treated of 6% urea solution that used in the second step research could be increased their digestibility and fermentability by supplementation of 10% sengon leaf.